Information Transparency of the Statement of Comprehensive Income: The Reporting Practice of WIG30 and DAX Companies - Jacek Gad (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This article aims to identify changes in the form of the statement of comprehensive income in companies in the WIG30 and DAX indices. It also aims to identify and grade components of other comprehensive income, in terms of the information transparency of the presentation options. The article demonstrates also the impact of national cultural dimensions on the form of the statement of comprehensive income. The study found that most of the surveyed companies present their statement of comprehensive income in two statements, with the number of accounting notes regarding comprehensive income presented by companies in their financial statements increasing over the period under study. The study identified four options for the presentation of other comprehensive income components used by the surveyed companies in the years 2012-2014, with the particular option chosen reflecting the different information transparency of the statement of comprehensive income. The results show that the practice of reporting in the area of the statement of comprehensive income of the DAX index companies is ahead of that in the WIG30 index. The research results on information transparency of the statement of comprehensive income correspond to one of the national cultural dimensions.